46‐3: Invited Paper: Design and Process of 2D Backlight Beyond HDR 5000 Nits. Issue 1 (28th June 2021) - Akimoto, Hajime; Yamamoto, Atsushi; Washio, Hajime; Nakano, Taketoshi
Abstract : HDR 2D‐backlight designs and some process for each of automotive/monitor, mobile device, and future Reality applications are presented. On‐chip lens and confining wall reflector structure are suitable for automotive/monitor applications, and 5, 000nits of peak brightness will be performed in real usage. The white LED chip architecture is proposed for mobile applications of 2‐1mm thin backlight. The power efficiency is evaluated to be almost double, and the 500lux ambient light contrast is 5 times larger than a 15.6‐inch OLED display. The 0.5mm thin film backlight with micro‐LED chips for Reality applications is proposed.